Geospatial modelling of relationships between select recreational user groups' social values and ecosystem services in the Cape Peninsula of South Africa. - Tonkin, Curtley Wayne (Stellenbosch : Stellenbosch University, 2023)
Thesis (MA)--Stellenbosch University, 2023.